2005
DOI: 10.1021/jp045080y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Temperature Dynamics of the Dimethylammonium Group in [(CH3)2NH2]3Sb2Cl9 on Proton Spin−Lattice Relaxation and Narrowing of the Proton NMR Line

Abstract: This paper reports the temperature dependence of the relaxation time T1 (55.2 and 90 MHz) and the second moment of the NMR line for protons in a polycrystalline sample of [NH2(CH3)2]3Sb2Cl9 (DMACA). The fundamental aspects of molecular dynamics from quantum tunneling at low temperatures to thermally activated reorientation at elevated temperatures have been studied. The experimentally observed spin-lattice relaxation rate is a consequence of dipolar interactions between the spin pairs inside the methyl group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…Neither can these signals arise from any magnetic field-dependent level mixing. Modulation depth decreased above 30 K, and the signals vanished at about 80 K. We speculated that they stem from tunnel splitting of the methyl groups (9). Tunneling sidebands have been observed in EPR spectra as early as 1972 (10), and the temperature dependence of the frequencies of our signals is akin to the one of methyl tunnel splitting observed by EPR (11) and electron nuclear double resonance (ENDOR) (12).…”
Section: Introductionmentioning
confidence: 51%
“…Neither can these signals arise from any magnetic field-dependent level mixing. Modulation depth decreased above 30 K, and the signals vanished at about 80 K. We speculated that they stem from tunnel splitting of the methyl groups (9). Tunneling sidebands have been observed in EPR spectra as early as 1972 (10), and the temperature dependence of the frequencies of our signals is akin to the one of methyl tunnel splitting observed by EPR (11) and electron nuclear double resonance (ENDOR) (12).…”
Section: Introductionmentioning
confidence: 51%
“…[8] have shown that at room temperature (293 K), (CH 3 ) 4 NGeCl 3 , here after abbreviated as TMAC-germanate, crystallizes in an orthorhombic modification (Pna2 1 ) with a = 13.096 Å, b = 8.911 Å, c = 9.128 Å and z = 4. The TMACgermanate has been reported [9] to reveal five phases in the temperature region 463-130 K, in which highest temperature phase being cubic perovskite structure above 424 K. Further, to understand the mechanism of phase transitions, the compound has been studied using alternating current (AC) conductivity, temperature dependent single crystal XRD and 35 Cl NQR/NMR techniques. [7] The title compound was also investigated by Winkler et al [10] using quasielastic and inelastic neutron scattering and Raman spectroscopic techniques and they observed the molecular reorientation of the whole tetramethylammonium (TMA) and methyl groups in the temperature region 446-4 K. Further, they have also observed that the structural phase transitions at 170, 200 and 424 K are unrelated to the temperature-induced changes of the molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…(21)) can be written as [46][47][48][49] 3 is caused by the over the barrier jumps. Because cos 2 Θ 3 ¼cos 2 (120 0 )¼ 1/4, the first reduction, is higher than the second reduction.…”
Section: Proton Spin-lattice Relaxation Timementioning
confidence: 99%